If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 + j = 50 Solving 22 + j = 50 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + j = 50 + -22 Combine like terms: 22 + -22 = 0 0 + j = 50 + -22 j = 50 + -22 Combine like terms: 50 + -22 = 28 j = 28 Simplifying j = 28
| 10+4x=17+15x+3 | | Z/7×5=8 | | 5-3x=-2x+9 | | Ax+bx=100 | | -3w+6=24 | | 3g=150 | | 6ln(2x)=15 | | (4x+26)= | | (Q-8)*3=15 | | Ax+box=100 | | f-33=67 | | 553+265=48 | | 9x-1=2x+48 | | 2h=28 | | 7x-63=2 | | 2(3x-4)+4x-3= | | 8+y=43 | | 4h=a | | Y+3x=16 | | -2x+2y=-3 | | 6a-12b+10b= | | 18b-54=54-3b | | j/4=7 | | Y/10=12 | | g(x)log1/3x | | 5(3x-5)+9=2(x+5) | | g-19=17 | | 50=0.5x^2-x+26 | | 5f=100 | | 24=0.5x^2-x | | 7(x-9)=2 | | X-3=6.5 |